2005
DOI: 10.1353/dem.2005.0023
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family structure transitions on youth achievement: Evidence from the children of the NlSY79

Abstract: We investigated the sensitivity of measures of cognitive ability and socioemotional development to changes in parents' marital status using data from the National Longitudinal Survey of Youth, 1979. We used several scores for each assessment, taken at different times relative to parents' marital transitions, which allowed us to trace the effects starting up to five years before a parent's change in marital status and continuing for up to six years afterward. It also allowed us to correct for the unobserved het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 20 publications
4
95
2
2
Order By: Relevance
“…Thomson and colleagues found that poorer economic resources accounted for some, but not all, of the detrimental effects of family structure on stepchildren's academic grades and socioemotional behavior. Race/ethnicity effects were also found in longitudinal analyses of the NLSY79 dataset (Aughinbaugh et al, 2005). For Latino American children, behavioral problems increased subsequent to the mothers' marriages, whereas this was not the case for European American or African American children.…”
Section: Stepfather Stepfamiliesmentioning
confidence: 82%
See 1 more Smart Citation
“…Thomson and colleagues found that poorer economic resources accounted for some, but not all, of the detrimental effects of family structure on stepchildren's academic grades and socioemotional behavior. Race/ethnicity effects were also found in longitudinal analyses of the NLSY79 dataset (Aughinbaugh et al, 2005). For Latino American children, behavioral problems increased subsequent to the mothers' marriages, whereas this was not the case for European American or African American children.…”
Section: Stepfather Stepfamiliesmentioning
confidence: 82%
“…Aughinbaugh, Pierret, and Rothstein (2005), using data on the marital transitions of young women recruited to the U.S. National Longitudinal Survey of Youth in 1979 (NLSY79) and subsequent data on their children's developmental outcomes, found a more substantial increase in behavioral problems following mothers' remarriages for girls than for boys. However, data from the Avon Longitudinal Study of Parents and Childhood (ALSPAC), an epidemiological study of 14,000 families in the United Kingdom, showed that, at Age 4, boys, rather than girls, in stepfather family settings displayed greater emotional and behavioral problems and less prosocial behavior, even after the quality of parent-child relationships, maternal history, and current socioeconomic status were controlled for (Dunn et al, 1998).…”
Section: Stepfather Stepfamiliesmentioning
confidence: 99%
“…Hence, if we observe an impact of parental divorce on children's cognitive skills (e.g., Kim 2011), at least beyond the early childhood years, it is likely influenced by the impact of psychosocial mediators, discussed below, on cognitive assessments. The evidence on the effects of parental divorce on cognitive assessments in math, verbal, and general test scores is mixed, with studies adopting more stringent tests for causal associations suggesting little or no effect (Aughinbaugh, Pierret, and Rothstein 2005;Cherlin et al 1991;Lee and McLanahan 2015;Morrison and Cherlin 1995;Sun 2001;Sun and Li 2002).…”
Section: Mediating Effects Of Parental Divorce On Children's Outcomesmentioning
confidence: 99%
“…Several prior studies have used data from the NLSY to investigate the impact of parental divorce (e.g., Aughinbaugh et al 2005;Lang and Zargorsky 2001;Morrison and Cherlin 1995).…”
Section: Data National Longitudinal Survey Of Youthmentioning
confidence: 99%
See 1 more Smart Citation